2014
DOI: 10.1111/ger.12151
|View full text |Cite
|
Sign up to set email alerts
|

Cost‐related dental non‐attendance in older adulthood: evidence from eleven European countries and Israel

Abstract: The findings of the present study suggest that a relatively small proportion of dental non-attendance in older adulthood is cost-related. For specific population subgroups in various countries, however, dental care costs may still pose a relevant barrier to dental care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 33 publications
1
11
0
1
Order By: Relevance
“…There is a lack of studies investigating specifically the postponement of dental visits due to cost-related reasons longitudinally [2], and this paper extends our current knowledge on this topic in older adults in Germany.…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations
“…There is a lack of studies investigating specifically the postponement of dental visits due to cost-related reasons longitudinally [2], and this paper extends our current knowledge on this topic in older adults in Germany.…”
Section: Discussionmentioning
confidence: 75%
“…Furthermore, this study observed that postponement of dental visits due to costs was not associated with self-rated general health but instead was associated with having fewer chronic diseases. Interestingly, Listl et al reported that cost-related non-attendance was associated with worse general health in older adults using the first wave of the SHARE Project [2]. However, it should be noted that this study did not report results on the number of chronic diseases and used aggregated data from 11 European countries in its statistical analyses.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Many previous authors have pointed out that the high cost of dental treatment is the most common reason for delaying or not receiving dental care [1011]. Although oral reconstruction is a prerequisite for enhancing the quality of life and general health of the elderly, its application is sometimes restricted by the dental health insurance coverage, income, financial status, and oral health status of those older than 65 years [1213].…”
Section: Discussionmentioning
confidence: 99%